2014
DOI: 10.1371/journal.pntd.0003046
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Praziquantel, Tribendimidine and Mebendazole in Patients with Co-infection of Clonorchis sinensis and Other Helminths

Abstract: BackgroundBoth tribendimidine and mebendazole are broad-spectrum drugs for anti-intestinal nematodes. We aim to assess the efficacy and safety of tribendimidine and mebendazole in patients with co-infection of Clonorchis sinensis and other helminths.MethodWe performed a randomized open-label trial in Qiyang, People's Republic of China. Eligible participants were randomly assigned to one of four groups: (i) a single dose of 400 mg tribendimidine, (ii) 200 mg tribendimidine twice daily, (iii) 75 mg/kg praziquant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 23 publications
0
27
0
Order By: Relevance
“…6, is a symmetrical diamidine derivative, of amidantel which was developed in China for use in humans in the mid-1980s. It is a broad-spectrum anthelmintic effective against soil-transmitted helminthiasis including hookworm, pinworms, roundworms, Strongyloides and flatworms (Xiao et al, 2005; Xu et al, 2014) of humans. Molecular studies (Hu et al, 2009) on C. elegans using null-mutants of the levamisole receptor subunits strongly suggested that tribendimidine is a cholinergic agonist that is selective for the same nematode muscle nAChR as levamisole.…”
Section: Tribendimidinementioning
confidence: 99%
“…6, is a symmetrical diamidine derivative, of amidantel which was developed in China for use in humans in the mid-1980s. It is a broad-spectrum anthelmintic effective against soil-transmitted helminthiasis including hookworm, pinworms, roundworms, Strongyloides and flatworms (Xiao et al, 2005; Xu et al, 2014) of humans. Molecular studies (Hu et al, 2009) on C. elegans using null-mutants of the levamisole receptor subunits strongly suggested that tribendimidine is a cholinergic agonist that is selective for the same nematode muscle nAChR as levamisole.…”
Section: Tribendimidinementioning
confidence: 99%
“…To date, several drug candidates for trematodiasis have been tested on animals [6][7][8][9][10]. Among these, numerous drugs are under trials for clonorchiasis patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is the only new anthelmintic drug that has been approved for human use within the past 3 decades [87]. Tribendimidine has been shown in laboratory and clinical studies to have a broad spectrum of activity against several nematode, trematode and cestode species [84,8892]. The activity of tribendimidine against 20 helminth parasites has been documented [93].…”
Section: Introductionmentioning
confidence: 99%